2014
DOI: 10.1021/ed4003282
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of an “Organic First” Chemistry Curriculum at a Liberal Arts College

Abstract: The chemistry department at Washington & Jefferson College implemented an "organic first" curriculum in the fall semester of 2005. Assessment data suggest that the net impact of this change for the department and associated constituencies has been positive: (i) Student outcomes have generally not been impacted by the curricular change, though a significant improvement in student performance on a standardized analytical exam has been observed. (ii) The department has attracted more majors, and can use faculty r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…11 These curricular approaches infuse more descriptive chemistry at the introductory level on the premise that some students are deterred by the quantitative nature of traditional general chemistry curriculum. Finally, others advocate for a pedagogical approach, based on the argument that the issues related to general chemistry are best addressed by reconsidering the way we teach it, rather than moving or eliminating it from the curriculum altogether.…”
mentioning
confidence: 99%
“…11 These curricular approaches infuse more descriptive chemistry at the introductory level on the premise that some students are deterred by the quantitative nature of traditional general chemistry curriculum. Finally, others advocate for a pedagogical approach, based on the argument that the issues related to general chemistry are best addressed by reconsidering the way we teach it, rather than moving or eliminating it from the curriculum altogether.…”
mentioning
confidence: 99%
“…'Organic first' curricula have been developed by Juniata College in Pennsylvania and by the University of Michigan, and biology-focused introductory chemistry sequences are offered at several universities, including Harvard and Purdue [13][14][15][16] . At most institutions, however, curricular change has been slow or nonexistent.…”
Section: Designing Convergent Chemistry Curriculamentioning
confidence: 99%
“…Washington & Jefferson College implemented this "organic first" curriculum in 2005 and found that it had a net positive impact on their students. 12 They did however need to restructure their organic chemistry courses significantly to allow for the added time in covering general chemistry topics that are typically reviewed quickly at the beginning of second year organic chemistry courses. The University of Michigan still offers a general chemistry course for students with a limited chemistry background, but if the students can show a strong enough chemistry background through their AP scores or via a placement exam, they can go directly to a more organic chemistry oriented sequence called "Structure and Reactivity".…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another approach that some institutions have taken is to drop introductory general chemistry altogether and incorporate the general chemistry material into other chemistry courses along the curriculum. Washington & Jefferson College implemented this “organic first” curriculum in 2005 and found that it had a net positive impact on their students . They did however need to restructure their organic chemistry courses significantly to allow for the added time in covering general chemistry topics that are typically reviewed quickly at the beginning of second year organic chemistry courses.…”
Section: Introductionmentioning
confidence: 99%